IMPROVING MEASUREMENT SKILLS IN EARLY CHILDHOOD THROUGH MANIPULATIVE MEDIA - Ani Melyawati, Eneng Sri Susilawati, Suci Aprilyati Ruiyat (JURNAL PENDIDIKAN DAN PENELITIAN SERUMPUN MENGAJAR, 2024)
The background of this research is based on the fact that the ability to subtract is still not optimal, this can be seen that there are still some children who experience difficulties when asked to name measuring instruments, especially if done randomly, children still go back and forth in naming and estimating sizes, Even during distance estimating activities, there are still some children who experience difficulty in choosing tools to measure distance. This is caused by the lack of methods and media used in the learning process at PAUD SPS Ahsahri Kopi V Kec. Kopo District. Serang Especially in measurement, the media used by teachers is less varied, and the learning process still uses classical learning which makes children bored so that learning becomes hampered. To improve measurement skills in children aged 5-6 years at PAUD SPS Ahsahri Kopi V Kec. Kopo Serang Regency through manipulative media. The aim of this research is to find out how to improve measurement skills in group B children and to see the use of manipulative media in improving measurement skills in group B children at PAUD SPS Ahsahri Kopi V. The method used in this research is Classroom Action Research (PTK), the implementation of which is in the form of exercises carried out in the classroom and also monitoring in the field, and includes relatively independent planning on a regular, continuous basis starting from planning, implementation, observation, reflection. The results of this research are that embedded board media can improve measurement skills in children aged 5-6 years at PAUD SPS Ahsahri Kopi V Kopo. The results of the increase obtained from the pre-research were analyzed, the percentage of children's measurement ability was 56%, then for cycle I the percentage result was 74.5%. For cycle II, the results obtained were 87.1%. From this data it can be said that the percentage of pre-research data in cycle I increased by 17.2%, then in cycle II there was an increase of 10.6%, so overall in this action research activity each cycle experienced an increase. Using the reference of completeness, children's learning outcomes are 75% - 80%. The success rate of increasing the reduction ability from this research is 76%.